An unpaired pickup and delivery problem with time dependent assignment costs: Application in air cargo transportation - Azadian, Farshid; Murat, Alper; Chinnam, Ratna Babu (European journal of operational research, 2017)
•A new pickup and delivery problem class with real-world application in air cargo.•A novel decomposition solution algorithm is proposed and tested.•Detailed computational experiments and results are presented.•Opportunities for future research are discussed. This study considers a freight forwarder's operational implementation of alternative access airport policy in a multi-airport region for cargo transportation. Given a set of heterogeneous air cargo customers, the forwarder's problem is to simultaneously select air cargo flight itineraries and schedule the pickup and delivery of customer loads to the airport(s). This problem is formulated as a novel pickup and delivery problem, where the delivery cost is both destination and time dependent. A mixed-integer linear model in presented and an efficient solution method based on decomposition is developed. The performance of the solution algorithm is evaluated by computational experimental study.